Highlights of the 31st annual meeting of the Society for Immunotherapy of Cancer (SITC), 2016. Issue 1 (18th July 2017) - Gulley, James L.; Repasky, Elizabeth A.; Wood, Laura S.; Butterfield, Lisa H.
Abstract : Abstract: Therapeutic efforts to engage the immune system against cancer have yielded exciting breakthroughs and a growing list of approved immune-based agents across a variety of disease states. Despite the early successes and durable responses associated with treatments such as immune checkpoint inhibition, there is still progress to be made in the field of cancer immunotherapy. The 31st annual meeting of the Society for Immunotherapy of Cancer (SITC 2016), which took place November 11–13, 2016 in National Harbor, Maryland, showcased the latest advancements in basic, translational, and clinical research focused on cancer immunology and immunotherapy. Novel therapeutic targets, insights into the dynamic tumor microenvironment, potential biomarkers, and novel combination approaches were some of the main themes covered at SITC 2016. This report summarizes key data and highlights from each session.